ISSUES IN FOREIGN LANGUAGE INSTRUCTION FOR STUDENTS OF AGRICULTURE AND ZOOENGINEERING SCIENCES - Eshchanov Marat Urazaliyevich (Zeta Repository, 2023)
In this article, actual problems in teaching a foreign language to students studying in the field of agriculture and zoo engineering, issues related to the lack of literature, information resources, the importance of teaching foreign languages in these fields are analyzed.